PENERAPAN MEDIA PEMBELAJARAN VIDEO PADA POKOK BAHASAN FUNGI TERHADAP KEMAMPUAN KOGNITIF SISWA SISWA SMA NEGERI 2 KARANGANYAR - Nurhayati, Ika; Muzayyinah, Muzayyinah; Karyanto, Puguh (Pendidikan Biologi, 2011)
ABSTRACT ? This research aims to find out the effectof the implementation of  learning media video on the  discussion subject fungi towards cognitive performance of the Xth grade students SMA Negeri 2 Karanganyar. This study is a quasi-experimental studies which use  Posstest Only Control Group Design. The independent variable in this research is the application of learning media videowhereas the dependent variable is students cognitive performance. The population of the study is the entire class X at SMA Negeri 2 Karanganyaracademic year 2011/2012.The samplesare taken towards control and treatment group. The sample is taken by using  Cluster Random Sampling method. The data collecting technique of implementation of the research result towards the learning process of biology used documentation and test. The test of the hypothesis for  the implementation of the research result towards the learning process of biology used T test. The result shows that the implementation of learning media videoare not influential towards cognitive performance of the Xth grade students SMA Negeri 2 Karanganyar Keywords: Learning Media, Video, Cognitive Perfomance